PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Paramita, Andina Dwi; Marsono, Marsono (Diponegoro Journal of Accounting, 2014)
The objective of this research was to analyze which characteristics of corporate governance that influence the extent of corporate social reponsibility (CSR) disclosures in the companies which operate in the mining and mining service sector in Indonesia. Corporate governance charecteristics which were used, namely size of board of commissioner, independent commissioner, composition of women on board, audit committee, ownership concentration, managerial ownership, foreign ownership, government ownership, and public ownership. The extent of CSR disclosure was measured using corporate social disclosure index (CSDI) based on Global Reporting Initiative (GRI) reporting standard items which were dislosed in companies’ annual report. This research also used firm’s size and profitability as control variables.The population of this research are companies which operate in the mining and mining service sector that listed in Indonesian Stock Exchange (IDX) in the period 2010 until 2012. Using purposive sampling method, then total sample of this research became 48 annual reports of mining companies. Multiple regression method was used to analyze the relationship between corporate governance characteristics and CSR disclosure.The results show that composition of women on board and managerial ownership has a significant effect toward the extent of CSR. The results also show that both of control variables have significant effects on the extent of CSR.